Eficiência na arrecadação de ICMS entre os segmentos no estado da Paraíba: um estudo a partir da implantação das notas fiscais eletrônicas - Oliveira, Rodrigo Pereira De (2017)
The present study proposed to investigate the efficiency of the levy of the tax named Tax on Operations Related to the Circulation of Goods and Interstate, Intermunicipal and Communication Services (Imposto sobre Operações Relativas a Circulação de Mercadorias e Serviços de Transporte Interestadual, Intermunicipal e de Comunicação - ICMS) at the State of Paraiba, based on information from the State Secretary of Revenue (Secretaria de Estado da Receita/PB - SER/PB). The efficiency estimated aimed to identifying key levy factors, disaggregated into 597 subclasses, by using the National Classification of Economic Activities (Classificação Nacional de Atividades Econômicas - CNAE), for the period from January 2013 to December 2015. Precisely, two models of Stochastic Frontier Analisys (SFA) using functional forms of Cobb-Douglas, based on the information of the Electronic Invoice System (Notas Fiscais Eletrônicas - NF-e), implemented since 2013. Variables were used to possibly explain the levy of the ICMS by the type of sectors (CNAE) in the state of Paraíba. We estimated a model with two stages, with the first being composed of the efficiencies estimations, and the second composed by estimations of the causes of technical inefficiency. The results revealed that the average of the technical efficiency of the state was 73.75% of the total potential ICMS, and the amount of tax evaded were around R$3.5 billion. Among the most efficient sectors, with efficiency above 90%, are those of wholesale commerce of ethanol, biodiesel, gasoline; distribution of electricity; fixed telecommunication services; cellular mobile telephony; and wholesaler of cigarettes. This result was observed mainly because the ICMS in these cases are collected in their respective sources. On the other hand, it was observed the existence of technical inefficiency in the levy in important sectors of the economy of the state of Paraíba, about which 93.17% is in consequence of the inefficiency of levy itself, and is motivated by the complexity of the tax system, increasing in the number of employees and negatively related to the concentration of the sector. It arouse mainly from the commerce of clothing and footwear, with large amounts evaded. In addition, it was verified that an increase of supervision actions inhibit the evasion increasing the collection, both in the form of actions or strategies.